2023
DOI: 10.1021/acsomega.3c06142
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of TiO2 Using Impatiens rothii Hook.f. Leaf Extract for Efficient Removal of Methylene Blue Dye

Getye Behailu Yitagesu,
Dereje Tsegaye Leku,
Getachew Adam Workneh

Abstract: In this work, TiO2 nanoparticles (NPs) were effectively synthesized by a green method using the Impatiens rothii Hook.f. leaf (IL) extract as a capping and reducing agent. The as-synthesized TiO2 NPs were characterized by different characterization methods such as the Brunauer–Emmett–Teller (BET) analysis, high-resolution transmission electron microscopy (HRTEM), scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX), Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 77 publications
(121 reference statements)
0
2
0
Order By: Relevance
“…The average particle size calculated from the TEM analysis is more than the average crystalline size obtained from XRD data using Scherrer equation, possibly because of aggregation and agglomeration effect. After getting attached, two or more than two particles give this effect [22]. The Selected Area Electron Diffraction (SAED) pattern of both the TiO 2 chemically synthesized and green synthesized confirmed that the nanoparticles vibration [19,45].…”
Section: Transmission Electron Microscopy Analysis Of Tio 2 Nanoparticlementioning
confidence: 88%
See 1 more Smart Citation
“…The average particle size calculated from the TEM analysis is more than the average crystalline size obtained from XRD data using Scherrer equation, possibly because of aggregation and agglomeration effect. After getting attached, two or more than two particles give this effect [22]. The Selected Area Electron Diffraction (SAED) pattern of both the TiO 2 chemically synthesized and green synthesized confirmed that the nanoparticles vibration [19,45].…”
Section: Transmission Electron Microscopy Analysis Of Tio 2 Nanoparticlementioning
confidence: 88%
“…Many studies have reported that due to the many phytochemicals (phenolics, terpenoids, etc), plant extract can act as a reducing and stabilizing agent by converting metal salt into nano form [16,17]. There are many studies reported synthesis of metallic nanoparticles using plants extract of jasmine flower [18], papaya [19], Piper nigrum, Coriandrum sativum, Syzygium aromaticum [20], rosemary, ginger [21], Impatiens rothii [22], Terenna asiatica [23], Garcinia mangostana [24], Iranian propolis [25], mango [26].…”
Section: Introductionmentioning
confidence: 99%